Mapping traditional knowledge: Digital cartography in the Canadian north - Engler, N.J. (Nate J.); Scassa, T. (Teresa); Taylor, D.R. (Fraser) (Cartographica: The International Journal for Geographic Information and Geovisualization, 2013)
Digital cartography offers exciting opportunities for recording indigenous knowledge, particularly in contexts where a people's relationship to the land has high cultural significance. Canada's north offers a useful case study of both the opportunities and challenges of such projects. Through the Geomatics and Cartographic Research Centre (GCRC), Inuit peoples have been invited to become partners in innovative digital mapping projects, including creating atlases of traditional place names, recording the patterns and movement of sea ice, and recording previously uncharted and often shifting traditional routes over ice and tundra. Such projects have generated interest in local communities because of their potential to record and preserve traditional knowledge and because they offer an attractive visual and multimedia interface that can address linguistic and cultural concerns. But given corporations' growing interest in the natural resource